A theoretical and numerical investigation of warm-phase microphysical processes - Igel, Adele, author; van den Heever, Susan, advisor; Kreidenweis, Sonia, committee member; Rutledge, Steven, committee member; Oprea, Iuliana, committee member (Colorado State University. Libraries, 2015)
Several studies examining microphysical processes are conducted with an emphasis on further understanding warm-phase processes, particularly condensation. In general, these studies progress from simple to complex representations of microphysical processes in models. In the first study, a theoretical, analytical expression for the condensational invigoration, that is the invigoration in the warm-phase of a cloud due to changes in the condensation rate, of a polluted, cloudy parcel of air relative to a clean, cloudy parcel of air is developed. The expression is shown to perform well compared to parcel model simulations, and to accurately predict the invigoration to within 30% or less. The expression is then used to explore the sensitivity of invigoration to a range of initial conditions. It is found that the invigoration, in terms of added kinetic energy, is more sensitive to the cloud base temperature than to the initial buoyancy of the parcels. Changes in vertical velocity between clean and polluted parcels of up to 4.5 m s−1 at 1 km above cloud base are theoretically possible, and the difference in vertical velocity decreases when the initial vertical velocity of either parcel is large. These theoretical predictions are expected to represent an upper limit to the magnitude of condensational invigoration and should be applicable to both shallow cumulus clouds as well as the warm phase of deep convection. In the second study, the focus shifts to the comparison of the representation of microphysical processes in single- and double-moment microphysics schemes. Single-moment microphysics schemes have long enjoyed popularity for their simplicity and efficiency. However, it is argued that the assumptions inherent in these parameterizations can induce large errors in the proper representation of clouds and their feedbacks to the atmosphere. For example, precipitation is shown to increase by 200% through changes to fixed parameters in a single-moment scheme and low cloud fraction in the RCE simulations drops from ~15% in double-moment simulations to ~2% in single-moment simulations. This study adds to the large body of work that has shown that double-moment schemes generally outperform single-moment schemes. It is recommended that future studies, especially those employing cloud-resolving models, strongly consider moving to the exclusive use of multi-moment microphysics schemes. An alternative to multi-moment schemes is a bin scheme. In the third study, the condensation rates predicted by bin and bulk microphysics schemes in the same model framework are compared in a novel way using simulations of non-precipitating shallow cumulus clouds. The bulk scheme generally predicts lower condensation rates than does the bin scheme when the saturation ratio and the integrated diameter of the droplet distribution are identical. Despite other fundamental disparities between the bin and bulk condensation parameterizations, the differences in condensation rates are predominantly explained by accounting for the width of the cloud droplet size distributions simulated by the bin scheme which can alter the rates by 50% or more in some cases. The simulations are used again in the fourth study in order to further investigate the dependency of condensation and evaporation rates to the shape parameter and how this dependency impacts the microphysical and optical properties of clouds. The double-moment bulk microphysics simulations reveal that the shape parameter can lead to large changes in the average condensation rates, particularly in evaporating regions of the cloud where feedbacks between evaporation and the depletion of individual droplets magnify the dependency of the evaporation rate on the shape parameter. As a result the average droplet number concentration increases as the shape parameter increases, but changes to the cloud water content are small. Taken together, these impacts lead to a decrease in the average cloud albedo. Finally, the simulations indicate that the value of the shape parameter in subsaturated cloudy air is more important than the value in supersaturated cloudy air, and that a constant shape parameter may not be a poor assumption for simulations of non-precipitating shallow cumulus clouds.